Examination of skin-fermented natural wines - Bene Zsuzsanna; Oláhné-Horváth Borbála; Kneip Antal; Balling Péter (WESSLING Nemzetközi Kutató és Oktató Központ Közhasznú Nonprofit Kft. Budapest, 2022)
The ancient white winemaking technology, kvevri, is gaining more and more attention among consumers, not only because it is unique and special, but also because sustainability and closeness to nature are fundamental characteristics of this winemaking process. This is also shown by the fact that the traditional clay pot, ancient Georgian process was added to the UNESCO list of Intangible Cultural Heritage of Humanity in 2013, and in 2020 the International Office of Viticulture and Oenology (OIV) included white wine fermented on skins in the category of special wines. This wave is also present in Hungary, since natural wine and orange wine have already appeared in the 2021 legislation as Other terms of limited use. The essence of the wine-making process is fermentation on the skins and micro-oxidation, the vessels of which can be various: amphora or kvevri, ceramic egg, spin barrel, depending on this, the chemical composition of the wines can change, as well as the formation of the precursor compounds of the aroma components. In the study, natural wines produced in the Tokaj wine region from the use of amphora and ceramic egg vessels were examined.
Keywords: Műszaki és technológiai tudományok; Egyéb műszaki tudományok és technológiák; Élelmiszer és italfélék